Elevated CO2 Enhanced the Antioxidant Activity and Downregulated Cell Wall Metabolism of Wolfberry (Lycium barbarum L.) - Ze Liang; Zisheng Luo; Wenxuan Li; Mingyi Yang; Lei Wang; Xingyu Lin; Li Li (MDPI AG, 2021)
Modified atmosphere packaging (MAP) has been widely known to delay the postharvest fruit senescence; nevertheless, its effect on antioxidant activity and cell wall metabolism of wolfberry fruit is largely unknown. The present study investigated the impact of elevated CO2 on the quality attributes and cell wall degradation of wolfberry fruit during storage. The results showed that 10% CO2 better maintained the physiological quality and conferred the reduction in weight loss, decay index, and color change. Higher 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and 1,1-diphenyl-1-picrylhydrazil (DPPH) radical scavenging activity, total phenol and flavonoid content, and superoxide dismutase (SOD) and catalase (CAT) activity of wolfberry were detected at elevated CO2 concentrations. Elevated CO2 atmosphere contributed to the maintenance of the cell integrity, the decrease of cell wall degradation (polygalacturonase, pectate lyase, cellulase, and β-glucosidase), and the increase of cellulose and proto pectin content. Overall, we revealed the potential mechanism of elevated CO2 on the antioxidant activity enhancement and cell wall homeostasis of fresh berry fruit.